2019
DOI: 10.1002/epi4.12306
|View full text |Cite
|
Sign up to set email alerts
|

The provision of epilepsy care across Europe 2017: A 17‐year follow‐up survey

Abstract: Summary Objective To assess the resources available in the provision of epilepsy care across Europe and the developments since the International League Against Epilepsy (ILAE) survey published in 2003 (data collected in 2000). Methods An updated online version of the European Epilepsy Services Inventory was distributed to all European chapters of the ILAE (N = 47) and responses were obtained from 33 chapters (response rate 70%). To assess trends and allow comparisons with the survey published in 2003, the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
(6 reference statements)
0
7
1
Order By: Relevance
“…It was also more common for persons with a high SES to be treated by a neurologist, raising questions about equal access to care. One important aspect reducing access to neurologists may be the low number of neurologists in Sweden -approximately 50 per million inhabitants, compared to the recently reported EU median of 79 per million inhabitants [16]. In the present study, poorer access to neurologist was seen in patients with low income, compared to those with high income.…”
Section: Discussioncontrasting
confidence: 64%
“…It was also more common for persons with a high SES to be treated by a neurologist, raising questions about equal access to care. One important aspect reducing access to neurologists may be the low number of neurologists in Sweden -approximately 50 per million inhabitants, compared to the recently reported EU median of 79 per million inhabitants [16]. In the present study, poorer access to neurologist was seen in patients with low income, compared to those with high income.…”
Section: Discussioncontrasting
confidence: 64%
“…Inclusion criteria: (1) according to the guidelines for epilepsy prevention and treatment issued by the International League Against Epilepsy in 2017 [12], combined with clinical features, EEG, and auxiliary examination methods, patients were diagnosed with unilateral TLE; (2) °×°5 12. T2 relaxation diagram was calculated for each slice using T2 relaxation diagram, and hippocampal HCT2 were measured.…”
Section: Subjectsmentioning
confidence: 99%
“…34 Data from other parts of the world show a similar scenario. 35,36 This is deplorable for the patients who have to live with their disease despite available treatment options, as well as for care providers and the public, as multiple studies have shown the cost effectiveness of surgical care for appropriate candidates. 37 A future comprehensive algorithm for progressively escalating evaluations of epilepsy patients should hence be supported by health politics and insurance carriers as well.…”
Section: Hear the Call: The Needsmentioning
confidence: 99%